A tale of two types: Generalists vs. specialists in asset management - Zambrana, Rafael; Zapatero, Fernando (Journal of Financial Economics, 2021)
Management companies assign some portfolio managers to run funds within a single investment objective (i.e., specialists), and others to run funds across several investment objectives (i.e., generalists). Our results show that funds achieve higher performance when they appoint superior pickers as specialists and market timers as generalists. We argue that these decisions are the result of a better match of manager mandates with the way information is collected and processed in each investment strategy. Overall our results are consistent with decision-making in fund families that add value to their investors by aiming to optimally assign or reassign portfolio managers.